2019
DOI: 10.1016/j.bbmt.2019.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Cell Transplantation for Paroxysmal Nocturnal Hemoglobinuria in the Age of Eculizumab

Abstract: Paroxysmal nocturnal hemoglobinuria (PNH) is a rare, acquired clonal hematopoietic cell disease characterized by the destruction of hematopoietic cells through activation of the complement system with manifestations that can be lifethreatening including hemolysis, thrombosis, and marrow failure. Allogeneic hematopoietic cell transplantation (HCT) remains the sole cure for PNH, but eculizumab, a terminal complement inhibitor of C5, has been used to prevent complement-mediated hemolysis in patients with PNH sinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 42 publications
1
19
0
1
Order By: Relevance
“…Taken together, the substantial direct medical costs and medical-related absenteeism costs associated with PNH further suggest that disease activity may not be well controlled despite treatment with eculizumab, and that the burden of disease appears greater among TD eculizumab users relative to TF eculizumab users. However, some case studies have shown that treatment with eculizumab may contribute to a reduction of morbidity prior to and complications following allogeneic hematopoietic stem cell transplantation among patients with PNH [27,28]. Additional research is needed to further delineate the use of eculizumab in the setting of transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, the substantial direct medical costs and medical-related absenteeism costs associated with PNH further suggest that disease activity may not be well controlled despite treatment with eculizumab, and that the burden of disease appears greater among TD eculizumab users relative to TF eculizumab users. However, some case studies have shown that treatment with eculizumab may contribute to a reduction of morbidity prior to and complications following allogeneic hematopoietic stem cell transplantation among patients with PNH [27,28]. Additional research is needed to further delineate the use of eculizumab in the setting of transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective series of 55 PNH patients undergoing hematopoietic stem cell transplantation (HSCT) included two cases associated with MF. The reported overall survival at 5 years was 70%, although the outcome of these two patients is not specified ( 22 ). Regarding outcome, four out of the total 23 patients reported (17.4%) died due to acute lymphoblastic/myeloid leukemia progression ( 16 , 17 ), infections, or liver failure secondary to refractory Budd–Chiari syndrome ( 18 ).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Furthermore, multiple studies have shown no adverse effect of pre-HCT eculizumab therapy on engraftment in patients with paroxysmal nocturnal hemoglobinuria. 27,28 Mei et al 29 published their experience with post-HCT eculizumab prophylaxis in 8 patients with paroxysmal nocturnal hemoglobinuria, and Cooper et al describe 2 additional patients. 27 Nine of 10 patients engrafted without issue, whereas 1 patient experienced graft failure.…”
Section: Donor Chimerismmentioning
confidence: 99%